Malignant Rolandic-Sylvian Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
The diagnosis, treatment, and outcomes of seven children with a syndrome termed "malignant rolandic-sylvian epilepsy (MRSE)" are described following retrospective chart analyses of 24 patients who were studied with magnetoencephalography (MEG) and intracranial video-EEG (IVEEG) at The Hospital for Sick Children, Toronto, Canada.